“That’s where our future came from”: Mining, landscape, and memory in Rankin Inlet, Nunavut - Cater, Tara; Keeling, Arn (Études/Inuit/Studies, 2013)
AbstractBased on ethnographic and oral history research, this article investigates community experiences of historical and contemporary mineral development in the Arctic through an analysis of the cultural landscape of Rankin Inlet, Nunavut. The town was established in the 1950s around the North Rankin Nickel Mine—Arctic Canada’s first industrial mining operation. The mine’s rapid closure in 1962 dealt a devastating blow to the local economy, with about half the community staying in Rankin Inlet and struggling to make a living. In spite of the long period since closure, the mine’s influence is still present in the town’s built environment and cultural landscapes. Our research seeks to reveal the symbolic attachments both Inuit and long-term Qallunaat residents have formed with the post-industrial landscape. We argue that Rankin Inlet, as a community, is coming to terms with and (re)staking its claims to its industrial past, as part of contemporary efforts to manage the costs and benefits of new mineral development in the region.